Advanced numerical insight into the structural damage of masonry vaults under seismic excitation: two valuable case studies. (2017) - Milani, Gabriele; Valente, Marco; Alessandri, Claudio
Most recent earthquakes have demonstrated the high seismic vulnerability of monumental masonry buildings and, specifically, critical issues associated with complex structural elements like vaults. The main purpose of this paper is the analysis of how quadripartite vaults behave under horizontal loads and what their role is in the global seismic behaviour of historical constructions. The analysis is dealt with by referring to two different case studies: the Narthex of the Nativity Church in Bethlehem and the Fornasini tower in the North East of Italy. By means of ABAQUS, a proper finite elements model is implemented in order to assess the global structural behaviour of the structures. To this purpose, the seismic behaviour is directly evaluated thorough non-linear dynamic analyses and the obtained crack patterns are discussed thoroughly. A Concrete Damage Plasticity (CDP) constitutive model is used to properly account for damage phenomena and softening occurring on masonry during an earthquake.